Radiation Dose Audit of Common X-Ray Diagnostic Procedures of Patients and Implications for Cancer Incidence in Southwestern Nigeria (2016)
One of the objectives of x-ray examination is high quality images; however administered radiation doses may be harmful to patients‟ health. Data on radiation dose to patients are scarce, and thus hinder the determination of local and national reference dose levels specific to a country owing to the differences in patient anatomy and radiological practice among nationals of different countries. This study was therefore, designed to determine the patient doses, local reference dose levels and estimate cancer risk based on administered dose at selected radiodiagnostic centres in Southwestern Nigeria. Twelve radiodiagnostic centres were purposely selected across Lagos (3); Ogun (2); Oyo (1); Osun (4) and Ekiti (2) for this study. Exposure parameters including: peak voltage; tube load (mAs); focus-to-skin distance were obtained from x-ray machines during radiographic procedures. Quality control (QC) tests were performed using standard calibration method. Anthropometric data from 689 consented subjects were obtained for chest (353) Postero-Anterior (PA) and Antero-Posterior (AP) for abdomen (20), pelvis (35), skull (56), lumbar spine (87), thigh (12), leg (46), knee (17) and hand (63) examinations. Measurement of Entrance Surface Dose (ESD) was carried out with thermoluminescent dosimeters and converted to Dose-Area Product (DAP). Organ Dose (OD) and Effective Dose (ED) were determined using appropriate software. Organ doses were used to estimate the expected number of cancer incidences resulting from the examinations. Preliminary Local Reference Dose Levels (PLRDLs) were determined, and Patient Parametric-Exposure Estimation (PPEE) models which served as guides in the choice of appropriate exposure parameters for dose optimisation were developed. Data were analysed using descriptive statistics and compared with National Radiological Protection Board levels. The QC results showed that 66.7% of the x-ray machines fall within the internationally acceptable tolerance limit of ±5.0% of exposure parameters reproducibility. The ESD (mGy) for chest PA, abdomen AP, pelvis AP, lumbar spine AP, skull AP, leg AP, knee AP, hand AP and thigh AP were 2.32 ± 0.19, 11.72 ± 2.62, 4.05 ± 0.54, 4.74 ± 0.72, 7.07 ± 0.67, 1.27 ± 0.19, 1.59 ± 0.34 ± 0.19,0.50 ± 0.05; and the DAP (Gy cm2) were 3.06 ± 0.30,17.16 ± 4.96, 3.28 ± 0.47, 2.72 ± 0.44,4.53 ± 0.05,1.15,1.53 ± 0.23,0.92 ± 0.13,0.18 ± 0.02 for chest PA, abdomen AP, pelvis AP, lumbar AP, skull AP, leg AP, knee AP, hand AP and hand AP projections respectively The ED ranged from. The ranges of cancer incidences expected per annum for patients undergoing chest PA examinations for different organs were: lung (227-452), breast (28-207), easophagus (8-26), stomach (28-78) and liver (14-95). The proposed PLDRLs for ESD (mGy) and the corresponding DAP (Gy cm2) were;2.95(3.14), 22.31(28.59), 6.63(4.77), 5.87(3.20), 9.04(5.06), 1.51(2.04), 2.78(2.09), 2.39(1.44), 0.69(0.25) chest PA, abdomen, pelvis, lumbar spine, skull, leg, knee, hand and thigh (AP projections) respectively. The determined PLDRLs were higher than the National Radiological Protection Board reference levels by factors ranging from 1.70-19.70 and 2.20-31.40 for ESD and DAP, respectively. The developed models for estimating patient thickness from weight () were: for standard male and female adults respectively. Patients undergoing selected diagnostic x-ray procedures in Southwestern Nigeria received high doses and have increased risk of cancer. The established local reference levels could help in dose optimisation for radiological practices in Southwestern Nigeria.